Poetics of quilombola movement and interculturality: body and decolonial dances from the Freirean perspective (Práxis Educativa, 2022)
In this paper, the quilombola decolonial dances were analyzed from the Freirean perspective, based on the investigation of the aesthetic matrices and cultural motives that constitute the samba de roda and fandango caiçara. It was considered how the textualization of quilombola bodies express the decolonial perspective of dance. It is a historical investigation of the present time. Theoretical references, observations of artistic and cultural practices of quilombola dances were used, more specifically the samba de roda of the Quilombo Buri, Bahia; and the fandango of the Quilombo Batuva, Paraná. It was concluded that the interculturality expressed in the senses and meanings of decolonial dances unveils historicity and memories of the black Atlantic and diaspora and it is updated in the present time. The samba de roda of the Quilombo Buri reveals the production of inter-knowledge that highlights the safeguarding of culture, resistance and reinvention of knowledge. At the Quilombo Batuva, records of decolonial dance are historical. Fandango is not part of the quilombo’s artistic and cultural practices, but it signifies and translates the relations of education, body and culture of the community.Keywords: Dance. Decoloniality. Quilombo.